Pragmatics in Everyday Life: Understanding Unspoken Rules of Interaction - Rodiatul Audiyah Lubis; Deasy Yunita Sari Siregar; Putri Nabila Husni; Fitri Miftahul Rizky; Hidayatut Thomaroh (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Pragmatics, a fundamental branch of linguistics, focuses on the implicit rules that govern human interaction. It delves into how meaning is constructed, conveyed, and interpreted in everyday communication beyond literal language. This study explores the mechanisms of pragmatics in daily life, particularly how context, shared knowledge, and social conventions influence interactions. Key areas examined include speech acts, implicature, and politeness strategies, which highlight the dynamic nature of meaning-making in various social contexts. Speech acts, such as requests, apologies, and promises, illustrate how utterances perform actions beyond their lexical content. Implicature examines how individuals infer meaning that is not explicitly stated, relying on context and shared assumptions. Politeness strategies, which vary across cultures, play a crucial role in managing interpersonal relationships and ensuring smooth communication by balancing social expectations and individual intentions. Understanding these unspoken rules is essential for effective communication, as they often dictate the success of social interactions. Misinterpretations in pragmatics can lead to misunderstandings, social faux pas, or conflicts, emphasizing the importance of cultural and contextual awareness. Pragmatic competence is crucial in multilingual and multicultural settings, where differing conventions and norms can create unique challenges. By synthesizing theoretical insights from existing literature, this study highlights the pervasive influence of pragmatics in shaping human interaction. It underscores the necessity of pragmatic awareness in fostering interpersonal understanding, enhancing communication skills, and navigating the complexities of social life effectively.